Penguatan Pengetahuan dan Pendampingan Kesehatan Guru dan Karyawan dalam Pencegahan Penyakit Kardiovaskular - Umara, Annisaa Fitrah; Habibi, Alpan; Rosnaningsih, Asih (Universitas Malahayati Lampung, 2024)
ABSTRAK Penyakit kardiovaskular menjadi penyebab kematian global termasuk di Indonesia. Gaya hidup tidak sehat meningkatkan kemungkinan terjadi penyakit kardiovaskular di masa mendatang. Kelompok mayoritas yang kurang melakukan aktivitas fisik dan tinggi konsumsi gula yaitu di sekolah. Tujuan PKM sebagai penguatan pengetahuan dan pendampingan pada guru dan karyawan di SD Muhammadiyah 30 Poris Jaya–Tangerang. Kegiatan dilakukan terhadap 30 orang guru dan karyawan dengan metode pemeriksaan fisik, pre dan post test, seminar, dan FGD. Hasil mayoritas peserta perempuan, usia <34 tahun, tekanan darah normal, IMT 13.79–25.99 kg/m2, tidak merokok, tidak diabetes mellitus, dan tidak olahraga, faktor risiko rendah penyakit kardiovaskular menurut JCS. Mayoritas RLPP dan RLPTB perempuan meningkat, sedangkan RLPP laki-laki meningkat dan RLPTB dalam batas normal. Terdapat peningkatan nilai rata-rata pengetahuan. Mayoritas peserta mampu menghitun skor risiko penyakit kardiovaskular dengan JCS, dan menghitung RLPP-RLPTB. Kata Kunci: Pendampingan, Penguatan Pengetahuan, Penyakit Kardiovaskular ABSTRACT Cardiovascular disease is the cause of death globally, including in Indonesia. An unhealthy lifestyle increases the likelihood of cardiovascular disease in the future. One of the majority groups that does not do enough physical activity and consumes a lot of sugar is at school. The aim of PKM is to strengthen knowledge and provide assistance to teachers and employees at SD Muhammadiyah 30 Poris Jaya-Tangerang. Activities were carried out on 30 teachers and employees using physical examination methods, pre and post tests, seminars and FGDs. Results: The majority of participants were female, aged <34 years, normal blood pressure, BMI 13.79–25.99 kg/m2, did not smoke, did not have diabetes mellitus, and did not exercise. The majority of participants had low risk factors for cardiovascular disease. The majority of women's RLPP and RLPTB increased, while men's RLPP increased and RLPTB was within normal limits. There was an increase in the average knowledge score and the majority of participants were able to calculate cardiovascular disease risk scores using JCS and calculate RLPP-RLPTB independently. It is recommended that there be continuity of structured and scheduled activities as an effort to reduce risk factors for cardiovascular disease among teachers and employees at SD Muhammadiyah 30 Poris Jaya. Keywords: Accompaniment, Strengthening Knowledge, Cardiovascular Disease